A European Perspective: Potential of Grid and Storage for Balancing Renewable Power Systems. Issue 1 (27th November 2015) - Weitemeyer, Stefan; Kleinhans, David; Wienholt, Lukas; Vogt, Thomas; Agert, Carsten
Abstract: Increasing transmission grid capacities and the use of storage devices are two options often considered to balance the fluctuations originating from variable renewable energy sources (VRES) in power supply systems. We investigate which storage characteristics are most beneficial for integrating a high share of VRES into a fully connected European power system. By applying a modeling approach to long‐term meteorological and load data, we find that a suitable combination of solar and wind capacities permits the cost‐effective integration of very high shares of VRES if complemented with the installation of small, highly efficient storage systems and fully flexible backup capacities. Our simulations also show that the grid is used significantly for approximately 3/4 of the time to balance surpluses and deficits. The results emphasize that the expansion of the European transmission grid is an important option to consider for the reduction of the required balancing measures for integrating very high shares of VRES. Abstract : Storage matters! The installation of small storage capacities is highly beneficial for the integration of fluctuating renewable energy sources (RES) in a fully connected European power supply system. Our simulations are based on long‐term meteorological and load data and show that renewable energy sources can meet a very high share of the demand if they are combined with small and highly efficient storage capacities.